Puberty is an important developmental period for the establishment of adipose tissue mass and metabolic homeostasis. (3rd July 2017) - Holtrup, Brandon; Church, Christopher D.; Berry, Ryan; Colman, Laura; Jeffery, Elise; Bober, Jeremy; Rodeheffer, Matthew S.
ABSTRACT: Over the past 2 decades, the incidence of childhood obesity has risen dramatically. This recent rise in childhood obesity is particularly concerning as adults who were obese during childhood develop type II diabetes that is intractable to current forms of treatment compared with individuals who develop obesity in adulthood. While the mechanisms responsible for the exacerbated diabetic phenotype associated with childhood obesity is not clear, it is well known that childhood is an important time period for the establishment of normal white adipose tissue in humans. This association suggests that exposure to obesogenic stimuli during adipose development may have detrimental effects on adipose function and metabolic homeostasis. In this study, we identify the period of development associated with puberty, postnatal days 18–34, as critical for the establishment of normal adipose mass in mice. Exposure of mice to high fat diet only during this time period results in metabolic dysfunction, increased leptin expression, and increased adipocyte size in adulthood in the absence of sustained increased fat mass or body weight. These findings indicate that exposure to obesogenic stimuli during critical developmental periods have prolonged effects on adipose tissue function that may contribute to the exacerbated metabolic dysfunctions associated with childhood obesity.